Energy efficient catalytic CO2 desorption: mechanism, technological progress and perspective - Li, Ting; Yu, Qian; Barzagli, Francesco; Li, Chao'en; Che, Mingrui; Zhang, Zhien; Zhang, Rui (Carbon Capture Science & Technology, 2023)
High energy penalty in amine-based solvent regeneration process is a critical challenge in industrial application for post-combustion CO2 capture technology. Recently, many efforts have been made to devise strategies for lowering the energy requirement, such as using efficient blended amine systems to combine the advantages of different amines and/or adding the solid acid catalysts. This perspective aims at reviewing the most recent advances and opportunities to reduce the energy cost by applying various catalysts in solvent regeneration process. By analyzing non-catalytic CO2 regeneration mechanism in amine solutions (including single and blended amine solutions), we can further explore a plausible catalytic desorption mechanism over various catalysts in CO2-loaded amine solution. A wide range of different catalysts have been reported, including Brønsted/Lewis acid catalysts, acid-base bifunction catalysts, metal oxide catalysts, metal ion mediated catalysts, nanofluids absorbents and carbonic anhydrases, their performance in CO2-amine-water systems have been discussed in detail. The main analytical techniques for determining the peculiar physico-chemical properties of the catalysts have been described. The effects of catalysts on CO2 desorption performance of amine solvent systems regarding cyclic capacity, desorption rate and energy consumption are discussed in depth. Furthermore, the structure-activity relationships of the catalysts and their stability in continuous use have been carefully elaborated. Finally, the types of catalysts that assemble the highest quality and some considerations regarding the industrial implication of catalysts are illustrated. This review aims to provide guidance for the future development of efficient new catalysts. In this regard, the addition of solid acid catalysts in blended amine solution which are synthesized by loading metal oxide on supporting material, especially bi-functional catalyst, seems to be a recommendable strategy.